Rehabilitación del camino de acceso a la toma de aguas del Centro de Producción Hidroeléctrico Río Macho - Torres Montenegro, Danny (Instituto Tecnológico de Costa Rica, 2011)
The main objective of this work is the reconstruction of the access road to the Monte Cristo’s take of water in Río Macho, property of Instituto Costarricense de Electricidad (ICE). During the planning phase, it requires the development of geometric design stages, that is to draw the road having the knowledge of the current national regulations and the topography, roadway design, that involves roadway types and roadway types combinations analysis in accordance with the roadway requirements, secondary works (sewerage, ditches, etc) according to topography and rainfall conditions of the place; also is required site design of dumps to make an optimal management of the waste and bring enough environmental protection to have the minimum damage. Another objective is to estimate the cost of the work under an execution time program that involves all the activities and the necessary resources. The necessary materials are well graduated river gravel, sewer pipes and conventional concrete, as well as geosynthetics that improve the roadway structure efficiency and protect the slopes product of the road and the dump construction. Finally, making use of national employed techniques and with the use of the mentioned materials, the next step will be to make a proposal design of the road according to the arising needs.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2011.
Keywords: Razantes; Estabilización; Geosintéticos; Bases; Reforzamiento